Shipping Routes and Spice Trade in Southeast Sulawesi in the 17th and 18th Century - Susanto Zuhdi (Diponegoro University, 2018)
This paper discusses the dynamics of sea voyage and trade formed in the network of Southeast Sulawesi waters in the 17th and 18th century. Buton was chosen as a port that played the role in that network. Southeast Sulawesi as the concept of region will be positioned in the eastern and southern part of Sulawesi network, and other parts of the Nation. In addition to the strategic location connecting Makassar to North Maluku and Central Maluku, also spices as the commodities transported through this line, Buton has its own trade commodities, such as slaves, and iron tools (knives, machetes). Although it is not in large in numbers, cloves from Buton were also the target of VOC. As a collecting center port, Buton plays a role in the network of